The Relationship between Fear-Avoidance Beliefs and Pain in Pregnant Women with Pelvic Girdle Pain: A Cross-Sectional Study - Farzaneh Rashidi Fakari; Masoumeh Simbar; Marzieh Saei Ghare Naz (Shiraz University of Medical Sciences, 2018)
Background: Pelvic Girdle Pain (PGP) is one of the most common problems during pregnancy. Psychological variables including attitude, belief, cognition, and fear have more effects on risk factors for back pain, compared to biomechanical factors. Moreover, fear and anxiety may be provoked by the prospect of pain, which is associated with higher levels of disability, compared to pain itself. Therefore, this study aimed to investigate the relationship between fear-avoidance beliefs and pain in pregnant women with pelvic girdle pain. Methods: This descriptive cross-sectional study was conducted on 148 pregnant women with PGP, who referred to the healthcare centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran, Iran from September to December 2017. The samples were selected by the multi-stage method. Data collection tools included a demographic questionnaire, Pelvic Girdle Questionnaire (PGQ) and Fear-Avoidance Beliefs Questionnaire (FABQ). Data analysis was performed in SPSS version 22, using descriptive statistics, ANOVA, t-test and multiple regression. A P-value less than 0.05 was considered significant. Results: The subjects' mean age and gestational age were 29.35±5.89 years and 32.78±5.13 weeks, respectively. Mean and SD of Fear-Avoidance Beliefs (FAB) toward PGQ was 41.27±13.67 (from 66). In addition, PGQ was moderate in the majority of participants [84 (56.75%)]. Results of one-way ANOVA demonstrated a significant relationship between the mean total score and the score of dimensions of physical and occupational activities of FAB in different severities of PGQ (P<0.001). Conclusion: The results of this study indicated that fear-avoidance and catastrophic beliefs, in women with PGP can be predicted. According to the results of the study, FAB varied with the severity of pain. In addition, increased pain intensity was associated with elevated score of FAB.